2009
DOI: 10.1104/pp.109.145862
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity in Photosynthetic Temperature Acclimation among Crop Species with Different Cold Tolerances    

Abstract: While interspecific variation in the temperature response of photosynthesis is well documented, the underlying physiological mechanisms remain unknown. Moreover, mechanisms related to species-dependent differences in photosynthetic temperature acclimation are unclear. We compared photosynthetic temperature acclimation in 11 crop species differing in their cold tolerance, which were grown at 15°C or 30°C. Cold-tolerant species exhibited a large decrease in optimum temperature for the photosynthetic rate at 360 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 65 publications
(125 reference statements)
5
136
0
4
Order By: Relevance
“…While photosynthetic responses to climate change differ among species and genotypes [48,50,[61][62][63][64] the greater than expected acclimation of key photosynthetic processes reported here has important implications for C 3 photosynthesis beyond that of soybeans. Indeed, assessing the magnitude and direction of acclimation is crucial to our understanding of global carbon flux and food security because A modulates the largest exchange of carbon from the atmosphere into ecosystems and is an important determinant of crop yields.…”
Section: Resultsmentioning
confidence: 99%
“…While photosynthetic responses to climate change differ among species and genotypes [48,50,[61][62][63][64] the greater than expected acclimation of key photosynthetic processes reported here has important implications for C 3 photosynthesis beyond that of soybeans. Indeed, assessing the magnitude and direction of acclimation is crucial to our understanding of global carbon flux and food security because A modulates the largest exchange of carbon from the atmosphere into ecosystems and is an important determinant of crop yields.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cold-tolerant species such as winter wheat, spinach, etc. have the capacity to maintain a high level of CO 2 assimilation rate whereas sensitive cold species do not have this capacity (Yamori et al 2010). Gusta and Wisniewski (2013) reported that energy is an essential factor to drive acclimation and that sugars have important effects on plant freezing tolerance, resiliency of photosynthesis under stress condition.…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…The whole portable gas exchange system was enclosed in a temperature-controlled cabinet (Yamori et al, 2005(Yamori et al, , 2006a(Yamori et al, , 2008(Yamori et al, , 2010b. The CO 2 assimilation rate (A) versus intercellular CO 2 concentration (C i ) was measured at a light intensity of 1,200 mmol photons m 22 s 21 under several measurement temperatures.…”
Section: Gas Exchange and Fluorescence Measurementsmentioning
confidence: 99%